2019
DOI: 10.13189/ujer.2019.071512
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Network-Based PUMA Teaching-Learning Model on Information Literacy, Computational Thinking, and Communication Skills

Abstract: Network-based Preparing Un-coding Modifying and Adding (PUMA) is a teaching-learning model that focuses on communication among students rather than emphasizing programming language grammar in an online education platform. The Network-based PUMA model consists of four steps: preparing, un-coding, modifying and adding. The results of the PUMA model applied to the National University of Education's student teachers for six weeks show that students were able to maintain their information literacy skills and improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…W. Chan et al, 2020;Diago et al, 2021;Guo et al, 2016;Kim, 2021;Moreno-León et al, 2015;Noh & Lee, 2020;Pérez-Marín et al, 2018;Relkin et al, 2021;Sun, Hu, et al, 2021a). On the other side, various studies also showed the opposite results of computer technology in enhancing students' CT skills (Conde et al, 2017;Jeong & Sung, 2019;Kong et al, 2020;Pellas & Vosinakis, 2018;Zhao & Shute, 2019). In conclusion, the use of computer technology had various effect levels to the enhancement of students' CT skills.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…W. Chan et al, 2020;Diago et al, 2021;Guo et al, 2016;Kim, 2021;Moreno-León et al, 2015;Noh & Lee, 2020;Pérez-Marín et al, 2018;Relkin et al, 2021;Sun, Hu, et al, 2021a). On the other side, various studies also showed the opposite results of computer technology in enhancing students' CT skills (Conde et al, 2017;Jeong & Sung, 2019;Kong et al, 2020;Pellas & Vosinakis, 2018;Zhao & Shute, 2019). In conclusion, the use of computer technology had various effect levels to the enhancement of students' CT skills.…”
Section: Introductionmentioning
confidence: 95%
“…Some studies, however, revealed that the utilization of computer technology significantly does not enhance students' CT skills (Atmatzidou & Demetriadis, 2016;Barrón-Estrada et al, 2022;Bedar & Al-Shboul, 2020;Booth, 2013;Christian Puhlmann Brackmann et al, 2019;J. Chan & Nejat, 2012;Conde et al, 2017;Diago et al, 2021;Jeong & Sung, 2019;Kim, 2021;Kim & Kim, 2016;Kong et al, 2020;Pellas & Vosinakis, 2018;Sulistiyo & Wijaya, 2020;Sun, Hu, et al, 2021a;Wahyudin et al, 2021;Zhao & Shute, 2019). Moreover, a few of studies showed that the involvement of computer technology in learning process has a negative effect in enhancing students ' CT skills (del Olmo-Muñoz et al, 2020;Félix et al, 2020;Rodríguez-Martínez et al, 2020;Rose et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies have tended to evaluate the competency of the graduates in specific programmes such as Information Systems (Lavy & Rashkovits, 2019), Music (Eğilmez et al, 2019), Accounting (Erlane et al, 2018;Dunbar et al, 2016;Low et al, 2016), Business (Abbasi et al, 2018;Jackson & Chapman, 2012), Tourism (Tsai, 2017;Dhiman, 2012), Architecture (Rohani et al, 2016), Engineering (Triyono et al, 2018;Radhakrishnan & Sudha, 2015;Mohd Shamsuri & Izaidin, 2014;Mohd Shamsuri et al, 2013) and Information and Communication Technology (Mohd Shamsuri & Izaidin, 2014;Mohd Shamsuri et al, 2013). Other than that, some of the studies focused on the specific institutions (Jeong & Sung, 2019;Kalaivani et al, 2012) or specific regions (Khan, 2018;Triyono et al, 2018;Ting et al, 2017;Kahirol et al, 2016;Jackson & Chapman, 2012;Rahmah et al, 2011;Roselina, 2009;Andrews & Higson, 2008). While some of the studies only highlighted the graduates' soft skills in specific sectors such as industry (Khan, 2018;Kahirol et al, 2016), manufacturing (Shiau et al, 2018), banking (Abbasi et al, 2018) and service (Rahmah et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…2) ทดสอบก่ อนเรี ยนด้ วยแบบวั ดการรู ้ สารสนเทศในบริ บทของชุ มชน และ แบบประเมิ น ตนเองในการมี ส่ วนร่ วมในการเรี ยน 3) ดำเนิ นกระบวนการเรี ยนรู ้ ตามแผนการจั ดการเรี ยนรู ้ จำนวน 7 สั ปดาห์ ซึ ่ งจากงานวิ จั ยที ่ ผ่ านมาได้ ที ่ ได้ ศึ กษาผลของการรู ้ สารสนเทศทั ้ งในและต่ างประเทศแล้ วเกิ ดการเปลี ่ ยนแปลงของการรู ้ สารสนเทศ พบว่ างานวิ จั ยส่ วนใหญ่ ใช้ จำนวนสั ปดาห์ ในการดำเนิ นการทดลองเฉลี ่ ยอยู ่ ที ่ 4-10 สั ปดาห์ (Ashley, 2019;Bingham et al, 2016;Dennen et al, 2018;Hava & Gelibolu, 2018;Jeong & Sung, 2019;McCartin et al, 2019;Tsunekage et al, 2020;Weber et al, 2019;Young & Maley, 2018…”
Section: Gifting and Charityunclassified